Market Facilities and Agricultural Marketing: Evidence from Tamil Nadu, India - Shilpi, Forhad; Umali-Deininger, Dina (2012)
This article analyzes the effect of facilities and infrastructure available at the marketplace on a farmer's decision to sell at the market. The econometric estimation shows that the likelihood of sales at the market increases significantly with an improvement in market facilities and a decrease in travel time from the village to the market. The results suggest that wealth reduces a farmer's cost of accessing market facilities more than it increases her/his opportunity cost of leisure. The policy simulation indicates that the marginal benefits from an improvement in market facility will favor the poorer farmers in the context of India.